Adapting School-Based Substance Use Prevention Curriculum Through Cultural Grounding: A Review and Exemplar of Adaptation Processes for Rural Schools - Colby, Margaret (2013)
A central challenge facing twenty-first century community-based researchers and prevention scientists is curriculum adaptation processes. While early prevention efforts sought to develop effective programs, taking programs to scale implies that they will be adapted, especially as programs are implemented with populations other than those with whom they were developed or tested. The principle of cultural grounding, which argues that health message adaptation should be informed by knowledge of the target population and by cultural insiders, provides a theoretical rational for cultural regrounding and presents an illustrative case of methods used to reground the keepin’ it REAL substance use prevention curriculum for a rural adolescent population. We argue that adaptation processes like those presented should be incorporated into the design and dissemination of prevention interventions.